Efficacy and Safety of GLP-1 Receptor Agonists for Type 2 Diabetes Mellitus Treatment: Systematic Review - Ana Paula Martins; Rodrigo Miguel Martins Murteira (Formifarma, LDA., 2016)
Introduction: Glucagon-like peptide analogues are a new class of drugs used in the treatment of type 2 diabetes mellitus that mimic the endogenous hormone glucagon-like peptide 1. Glucagon-like peptide 1 regulates glucose levels by stimulating glucose-dependent insulin secretion, suppressing glucagon secretion, delayed gastric emptying and promoting satiety. The individualized treatment of type 2 diabetes mellitus, using various glucagon--like peptide receptor agonists, has recently been described and the interest related to these drugs continues to grow. Objectives: To review the efficacy and safety of glucagon-like peptide 1 agonists in patients with inadequately controlled type 2 diabetes mellitus on metformin alone, highlighting their added value in therapeutic use comparatively to second line oral therapies used in type 2 diabetes mellitus. Methods: Studies were obtained from electronic searches of The Cochrane Library and PubMed. Randomized controlled trials were selected if they were at least 8 weeks in duration; compared a glucagon-like peptide 1 analogue with an oral anti-diabetic agent in patients experiencing inadequate glycemic control with metformin monotherapy; and reported hemoglobin A1c data in non-pregnant adults with type 2 diabetes mellitus. Results: Of 72 potentially relevant articles identified, 23 were retrieved for detailed evaluation and 10 met the inclusion criteria. The majority of glucagon-like peptide 1 agonists showed equivalent or superior efficacy than most active comparators for reducing hemoglobin A1c, with a greater proportion of patients achieving hemoglobin A1c <7%. Glucagon-like peptide 1 agonists also showed extra-glycemic effects such as weight loss and the reduction of important cardiovascular parameters. Side effects included gastrointestinal complications, mainly nausea, vomiting and diarrhea. The incidence of hypoglycemia was less common for this class of agents. Conclusion: Glucagon-like peptide 1 agonists are an efficient and safe second-line option for treatment of type 2 diabetes.